Analisis Permintaan Agregat dan Penawaran Agregat: Perspektif Teori Dan Empiris - Sigalingging, Agustina Marlina Br; Sasmita, Puteri Keshya Adisty; Tamba, Rani Rosya; Rizkya, Sitta Mutia; Pane, Sanusi Ghazali (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze aggregate demand and aggregate supply from theoretical and empirical perspectives. A qualitative approach and literature study were used to collect relevant data. This research identifies factors that influence aggregate demand and supply. The research results show that increasing aggregate demand can encourage economic growth and create jobs, but also has the potential to cause inflation. On the other hand, an increase in aggregate supply can stabilize prices and increase production. Case studies in Indonesia show an increase in aggregate demand and supply from 2021 to 2023, with household consumption as the main driver. This research provides a deeper understanding of macroeconomic dynamics and can help policymakers in designing effective economic strategies.